Pulse density modulated ZVS full-bridge converters for wireless power transfer systems - Li, Hongchang (2019)
Pulse density modulation (PDM) is an advanced technique for maximum efficiency point tracking of wireless power transfer (WPT) systems. By using PDM, both voltage regulation and efficiency maximization can be achieved without dc/dc converters. PDM is also compatible with the dual-side soft switching technique that utilizes resonant tanks and synchronous rectification. However, this soft switching technique depends on coupling and load conditions. Hard switching may occur when the coupling of coils gets stronger or the equivalent load is not properly controlled. To eliminate the dependence and ensure the soft switching under various operating conditions, this paper proposes a PDM zero-voltage-switching (ZVS) full-bridge converter for WPT systems. The converter employs a ZVS branch between switching nodes to provide a ZVS current, and uses a specially designed modulator to obtain the valid ZVS current waveforms. Experimental results verified the proposed operating principles and showed that the additional power loss caused by the ZVS current is insignificant. The overall efficiency of the WPT prototype was 93 ~ 73% when the power transfer distance was 0.1 ~ 0.4 m, among which up to 85% efficiency was observed when the distance equaled the coil diameter.